Running speed-induced changes in foot contact pattern influence impact loading rate - Breine, B.; Malcolm, P.; Galle, S.; Fiers, P.; Frederick, E. C.; De Clercq, D. (European Journal of Sport Science, 2019)
Purpose. We aimed to determine the effect of speed-induced changes in foot contact patterns on the vertical instantaneous loading rate (VILR). We hypothesized that transition runners, i.e. runners that shift towards a mid- (MF) or forefoot contact pattern (FF) when running speed increases, show smaller increases in VILR than non-transition runners, i.e. runners that remain with a rearfoot contact pattern (RF).